Organizational Learning Capabilities for Sustainable Performance: Evidence from Saudi Arabia's Public Sector - Majed Salem Alsuhaimi, (European Journal of Sustainable Development, 2025)
This study examines how knowledge management practices contribute to sustainable development outcomes in Saudi Arabia's public sector organizations. Using quantitative methodology, data was collected from 384 public sector employees across multiple organizations through stratified random sampling. Results demonstrate that knowledge management processes significantly influence sustainable performance, with the full model explaining 34.1% of variance in sustainability outcomes. Cultural dimensions significantly moderate knowledge management effectiveness, with some cultural factors enhancing and others constraining the relationship between knowledge processes and sustainable performance. Technology infrastructure positively influences SECI implementation. Mediation analysis reveals that SECI processes partially mediate the technology-performance relationship. Findings provide robust empirical evidence that systematic knowledge management approaches can enhance public sector sustainability when properly adapted to local contexts. The study offers practical insights for implementing sustainability initiatives in emerging economies while highlighting the importance of cultural adaptation in knowledge management systems. Keywords: knowledge management, sustainable development, SECI model, organizational learning, cultural dimensions, public sector sustainability